2015
DOI: 10.1073/pnas.1424420112
|View full text |Cite
|
Sign up to set email alerts
|

In vitro model for lytic replication, latency, and transformation of an oncogenic alphaherpesvirus

Abstract: SignificanceMarek’s disease virus (MDV) serves as a versatile small-animal model for herpesvirus-induced oncogenesis. Infection of target cells in vitro was impossible due to the short-lived nature of B and T cells, and analysis of infected cells ex vivo was hampered by their low frequencies. To overcome these limitations, we established an in vitro system that allows infection of target cells with MDV using stimuli that prolong the survival of B and T cells. Our system recapitulates the situation in vivo, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…Chicken primary B cells can be cultured in the presence of chicken CD40L Consistent with previous reports [11,19], we found that when chicken primary B cells were cultured in the presence of soluble chCD40L, the number and viability of the cells was significantly increased compared to when cells were cultured in the absence of chCD40L (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Chicken primary B cells can be cultured in the presence of chicken CD40L Consistent with previous reports [11,19], we found that when chicken primary B cells were cultured in the presence of soluble chCD40L, the number and viability of the cells was significantly increased compared to when cells were cultured in the absence of chCD40L (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…Key questions that remain unanswered are the basis for the increased pathogenicity of the vv strain and the mechanism of attenuation of cell culture-adapted strains. However, until recently it has not been possible to culture chicken primary B cells ex vivo because, when they are removed from the BF, they do not survive for long [11]. Consequently, it has not been possible to perform a thorough analysis of the interactions of chicken B cells with different strains of IBDV, and many pathogenesis studies to date have been conducted in vivo, where birds are infected and bursal tissues are harvested at necropsy for downstream analysis of gene expression [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key questions that remain unanswered are the basis for the increased pathogenicity of the vv strain and the mechanism of attenuation of cell-culture adapted strains. However, until recently, it has not been possible to culture chicken primary B cells ex vivo as, when they are removed from the BF, they do not survive for long (11). Consequently, it has not been possible to perform a thorough analysis of the interactions of chicken B cells with different strains of IBDV, and many pathogenesis studies to date have been conducted in vivo , where birds are infected and bursal tissues are harvested at necropsy for downstream analysis of gene expression (1217).…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding chicken CD40 ligand (chCD40L), a molecule responsible for B cell proliferation in vivo , was identified (18) and a soluble fusion protein containing its extracellular domain was subsequently shown to support the proliferation of chicken B cells in culture for up to three weeks (19). In 2015, Schermuly et al showed that chCD40L-treated B cells could be infected with Marek’s disease virus (11), demonstrating that the cells have the potential for studying the consequences of lymphotropic virus infection. Despite these successes, chicken primary B cell cultures have not yet been applied to the study of IBDV.…”
Section: Introductionmentioning
confidence: 99%